Karakterisasi Hasil Sintesis Fotokatalis TiO2 Dengan Metode Sol-Gel dan Hidrothermal Untuk Aplikasi Limbah Petroleum - Manja Nanda Resa Manja; Hasmalina Nasution; Zumrotun Nasihah; Tengku Finalia; Laila Rahmadanis; Prasetya Prasetya; Rahmadini Syafri; Sri Hilma Siregar (Sistem Informasi, 2022)
Petroleum waste (crude oil) has become one of the sources of pollution in the sea. The pollution caused comes from several factors, oil spills from tankers, deliberate disposal of irresponsible industries. The layer of crude oil on the surface of the air holds back gas exchange from the atmosphere and reduces the solubility of oxygen in the waters so that it interferes with the respiration and photosynthesis processes in phytoplankton which are food producers in the sea. This study aims to characterize the synthesized TiO2 photocatalyst material using two methods, namely Sol-Gel (SG) and Hydrothermal (HD) which will then be used for applications in petroleum waste. To determine effectiveness of TiO2 photocatalyst in reducing crude oil spills on the sea surface based on fatty oil parameter tests. The synthesis of TiO2 was carried out by the solgel method (SG) and the hydrothermal method (HD) at various temperatures of 300 oC, 500 oC, and 700 oC. Characterization of the material formed using the SEM-EDX instrument, showed that in general it is spherical in shape, and is composed of C, O and Ti elements. The maximum effectiveness of SG-300, SG-500, and SG-700 was able to reduce fat oil content by 57.19%, 66.14% and 41.42% while HD-300, HD-500, and HD-700 were able to reduce fatty oil content. maximum of 60.87%. , 56.41% and 45.68% in the 120 minute irradiation time. The results showed that the photodegradation process in petroleum waste treatment using TiO2 material was able to reduce the fat oil content.